Effect of Different Level of Stocking Density on Feed and Water Intake of Broiler Chicken - Sikder, S. K.; Majumder, S. C.; Halder, G. (International Journal of Bio-resource and Stress Management, 2023)
An experiment was conducted on the performance of commercial broiler chicken under different cage densities. Ninety six 21 days old broiler chickens (uniform weight) were randomly divided into four experimental groups, comprising of three replicates. Each replicate was consisted of eight birds. The birds were kept under four different cage densities, viz. control group (T1) having cage floor area about 11 birds m-2; T2 having cage floor area about 14.3 birds m-2; T3 having cage floor area about 18 birds m-2; and T4 having cage floor area about 21.5 birds m-2. Common basal diets and same feeding and watering space bird-1 were provided for each group. Considering the overall mean value of daily feed intake it was observed that the highest feed consumption was found in T1 group followed by T2, T3 and T4, respectively and in case of daily water intake it was observed that the birds kept with higher density (21.5 birds m-2) consumed highest amount water followed by 18, 14.3 and 11 birds m-2. It can be concluded that the daily feed intake was decreased and daily water intake was increased with increased stocking density.